The Effect of Spiritual Emotional Freedom Technique (SEFT) Therapy on Reducing Labor Anxiety in Primigravida - Emilia, Emilia (HM Publisher, 2024)
Labor anxiety is a psychological condition experienced by most maternity mothers. Childbirth anxiety can cause various negative impacts, such as prolonged labor, surgical delivery, and even maternal death. Spiritual emotional freedom technique (SEFT) therapy is a non-pharmacological therapy that can be used to reduce labor anxiety. This study aims to analyze the effect of SEFT therapy on reducing childbirth anxiety in primigravida. This research uses a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 26 primigravidas who were divided into two groups, namely the treatment group (13 people) and the control group (13 people). SEFT therapy was given to the treatment group for 3 sessions. The results of the study showed that there was a decrease in birth anxiety in the treatment group after being given SEFT therapy. This is indicated by the average value of labor anxiety in the treatment group, which decreased from 29.83 in the pretest to 21.77 in the posttest. Meanwhile, in the control group, the average value of labor anxiety did not change, namely 28.08 in the pretest and 28.08 in the posttest. Based on the results of this study, it can be concluded that SEFT therapy can reduce labor anxiety in primigravida.